Proteomic View of the Crosstalk between Lactobacillus mucosae and Intestinal Epithelial Cells in Co-culture Revealed by Q Exactive-Based Quantitative Proteomics - Pajarillo, Edward Alain B.; Kim, Sang Hoon; Valeriano, Valerie Diane; Lee, Ji Yoon; Kang, Dae-Kyung (Frontiers in Microbiology, 2017)
Lactobacilli are bacteria that are beneficial to host health, but information on communication between Lactobacilli and host cells in the intestine is lacking. In this study, we examined the proteomes of the Lactobacillus mucosae strain LM1, as a model of beneficial bacteria, and the intestinal porcine epithelial cell line IPEC-J2 after co-culture. Label-free proteomics demonstrated the high-throughput capability of the technique, and robust characterization of the functional profiles and changes in the bacteria and intestinal cells was achieved in pure and mixed cultures. After co-culture, we identified totals of 376 and 653 differentially expressed proteins in the LM1 and IPEC-J2 proteomes, respectively. The major proteomic changes in the LM1 strain occurred in the functional categories of transcription, general function, and translation, whereas those in IPEC-J2 cells involved metabolic and cellular processes, and cellular component organization/biogenesis. Among them, elongation factor Tu, glyceraldehyde 3-phosphate dehydrogenase, and phosphocarrier protein HPr, which are known to be involved in bacterial adhesion, were upregulated in LM1. In contrast, proteins involved in tight junction assembly, actin organization, and genetic information processing (i.e., histones and signaling pathways) were significantly upregulated in IPEC-J2 cells. Furthermore, we identified functional pathways that are possibly involved in host-microbe crosstalk and response. These findings will provide novel insights into host-bacteria communication and the molecular mechanism of probiotic establishment in the intestine.